1979
DOI: 10.1172/jci109408
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the factors that control the generation of triiodothyronine from thyroxine in rat liver and the nature of the defect induced by fasting.

Abstract: A B S T R A C T Studies were performed to explore the mechanism underlying the impaired generation of 125-I-3,5,3'-triiodothyronine (T3) from 1251-thyroxine (T4) (T3-neogenesis) in preparations of liver from rats fasted for 48 h and the prevention of this effect by the feeding of glucose. T3-neogenesis in livers from fasted animals and those fed chow or glucose was assessed in various mixtures of crude microsomal fractions with either buffer or cytosols. T3-neogenesis was mediated by an enzyme present in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 49 publications
4
38
0
1
Order By: Relevance
“…The particular sensitivity of T3 suggests that food restriction does not only affect thyroid secretion. A reduction of peripheral conversion of T4 to T3 has been reported in rats (Balsam and Ingbar, 1979 ;Chopra, 1980 ;Gavin et al, 1980 ;Balsam et al, 1981a, b ;Gavin and Moeller, 1983 ;Shank et al, 1984 (Suda et al, 1978 ;Hughes et al, 1984) and obese (Burman et al, 1979(Burman et al, , 1980Jaedig and Faber, 1982 ;Marugo et al, 1984) men and in sheep (Blum et al, 1980). However, during fasting reverse T3 levels dot not change (Blum and Kunz, 1981) or decrease (Tveit and Almlid, 1980) in calves.…”
Section: Introductionmentioning
confidence: 91%
“…The particular sensitivity of T3 suggests that food restriction does not only affect thyroid secretion. A reduction of peripheral conversion of T4 to T3 has been reported in rats (Balsam and Ingbar, 1979 ;Chopra, 1980 ;Gavin et al, 1980 ;Balsam et al, 1981a, b ;Gavin and Moeller, 1983 ;Shank et al, 1984 (Suda et al, 1978 ;Hughes et al, 1984) and obese (Burman et al, 1979(Burman et al, , 1980Jaedig and Faber, 1982 ;Marugo et al, 1984) men and in sheep (Blum et al, 1980). However, during fasting reverse T3 levels dot not change (Blum and Kunz, 1981) or decrease (Tveit and Almlid, 1980) in calves.…”
Section: Introductionmentioning
confidence: 91%
“…This may be because not enough samples were studied or that they were not collected at the exact postpartum time when the transient rise occurred. On the contrary, the frequent and precise sampling practiced by Davicco et al (1982) (Balsam and Ingbar, 1979 ;Kaplan and Utiger, 1978 ;Naito et al, 1981) and piglets (Slebodzinski et al, 1982), has been shown to result in a decrease of circulating T3 in these species (Chopra, 1980 ;Hastings and Zeman, 1979 ;Heinen et al, 1981 andSlebodzinski et al, 1982, respectively) ; this phenomenon has also been shown in humans (Azizi, 1978 ;Burman et al, 1979 ;Suda et al, 1978), adult sheep (Blum et al, 1980), growing bulls Tveit and Almlid, 1980), deer (Bahnak et al, 1981), chickens (May, 1978) …”
Section: Introductionmentioning
confidence: 99%
“…NADPH is known to be a cofactor of GSH generating system, and it has been a matter of controversy whether NADPH acts directly on T4 deiodination or indirectly via GSH formation. Balsam and Ingbar (2) proposed that NADPH promoted T4 deiodination within cytosol, by increasing the concentration of GSH through the action of glutathione reductase, because NADPH did not show any effect on microsomal fraction. The results of the present study and of our previous observations (18,19) conflict with those of Balsam and Ingbar.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast SH blocking agents such as thiouracil, N-5 ethylmaleinimide, iodoactamide andp-chloromercuribenzoate inhibit the reaction (5,10,13,14,(22)(23)(24). NADPH is also an important cofactor of T4 5'-deiodinase and changes in the enzyme activity are closely associated with the hexose-monophosphate pathway (2,10,18,19). In the fetal and neonatal period, hepatic T4 5'-monodeiodination is extremely low, which rises promptly after birth (3, 5, 9-1 1, 21, 25).…”
Section: Abbreviationsmentioning
confidence: 99%